Northanger Abbey - McDermid, Val (Grove Press, 2014)
In this modern retelling of Austen's classic, bookish minister's daughter Cat Morland joins her well-to-do friends in Edinburgh and falls for an up-and-coming lawyer who may harbor unsettling secrets.